What are you laughing at? (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
The text presents edition n. 26 of Móin-Móin Magazine - Studies in The Arts of Puppetry, with the theme Laughter and the grotesque in the Puppetry, listing the main questions that provoked the authors and presenting the synthesis of the published articles.
Keywords: laughter; grotesque; puppetry